Comparative Analysis of Surgical Exposure among Endoscopic Endonasal Approaches to Petrosectomy: An Experimental Study in Cadavers - Loymak, Thanapong; Belykh, Evgenii; Abramov, Irakliy; Tungsanga, Somkanya; Sarris, Christina E.; Little, Andrew S.; Preul, Mark C. (Journal of Neurological Surgery Part B: Skull Base, 2022)
Objectives Endoscopic endonasal approaches (EEAs) for petrosectomies are evolving to reduce perioperative brain injuries and complications. Surgical terminology, techniques, landmarks, advantages, and limitations of these approaches remain ill defined. We quantitatively analyzed the anatomical relationships and differences between EEA exposures for medial, inferior, and inferomedial petrosectomies.Design This study presents anatomical dissection and quantitative analysis.Setting Cadaveric heads were used for dissection. EEAs were performed using the medial petrosectomy (MP), the inferior petrosectomy (IP), and the inferomedial petrosectomy (IMP) techniques.Participants Six cadaver heads (12 sides, total) were dissected; each technique was performed on four sides.Main Outcomes and Measures Outcomes included the area of exposure, visible distances, angles of attack, and bone resection volume.Results The IMP technique provided a greater area of exposure (p < 0.01) and bone resection volume (p < 0.01) when compared with the MP and IP techniques. The IMP technique had a longer working length of the abducens nerve (cranial nerve [CN] VI) than the MP technique (p < 0.01). The IMP technique demonstrated higher angles of attack to specific neurovascular structures when compared with the MP (midpons [p = 0.04], anterior inferior cerebellar artery [p < 0.01], proximal part of the cisternal CN VI segment [p = 0.02]) and IP (flocculus [p = 0.02] and the proximal [p = 0.02] and distal parts [p = 0.02] of the CN VII/VIII complex) techniques.Conclusion Each of these approaches offers varying degrees of access to the petroclival region, and the surgical approach should be appropriately tailored to the pathology. Overall, the IMP technique provides greater EEA surgical exposure to vital neurovascular structures than the MP and the IP techniques.
Keywords: endoscopic endonasal approach; petroclival; petrosectomy; transpterygoid